Classroom teachers’ professional development activities within the scope of life long learning in Turkey - Erdem, Aliye; Koç, E. Seda (Uluslararasi Insan Bilimleri Dergisi, 2016)
Among all the factors affecting education, teachers have more important role in ensuring the effectiveness of the teaching process. Teachers’ professional development is a subject that directly affect the teaching process. Researches on the development of teaching profession indicate that professional training is a necessity for better education and better schools. Because if the teacher learns during performing the teaching profession, the quality of the education offered by the teacher will be higher. Teachers who develop themselves in terms of profession provide both a better education and a positive learning environment for the students. In this context, the aim of this research is to investigate the activities of the classroom teachers participate in Turkey in order to ensure their professional development. The study is prepared depending on the views of the classroom teachers. The data were obtained from the classroom teachers who teach 1, 2, 3, and 4. classes in public and private elementary schools in Ankara, in the 2014-2015 academic year. Questionnaire developed by the researchers was used for collecting the data.
Keywords: Classroom Teachers; Professional Development; Professional Development Activities; Life long Learning; Education; 4. Education